Implementation of Internal Control In Improving Retail Business Effectiveness - Hasibuan, Hasrul Azwar (Universitas Dehasen Bengkulu, 2025)
The implementation of internal control in enhancing the effectiveness of retail business is a crucial strategy for managing operational and financial activities. Internal control involves various policies, procedures, and systems designed to safeguard company assets, minimize the risk of fraud and errors, and improve efficiency and compliance in daily operations. One key aspect of internal control is inventory and stock management. With an effective system to monitor inventory, retail businesses can avoid stock loss or shortages, reduce unnecessary storage costs, and enhance customer satisfaction by consistently providing available products. Furthermore, internal control includes monitoring sales activities, cash management, and adherence to company policies and procedures. By ensuring strict control over cash receipts, credit card usage, and other financial transactions, retail businesses can reduce the risk of theft or financial loss, while maintaining customer trust and compliance with applicable tax regulations. Beyond operational aspects, internal control also encompasses human resource management in retail. Implementing clear policies and procedures regarding payroll, promotions, training, and employee discipline can improve team effectiveness, reduce inefficiency or misuse of resources, and maintain a healthy and professional work environment. Overall, effective internal control implementation can provide benefits such as improved operational efficiency, reduced financial risk, asset protection, and enhanced compliance, enabling retail businesses to optimize long-term growth and sustainability in a competitive market.